Diversity in engineering: tinkering, tailoring, transforming - GRIMSON, JANE BARCLAY; ROUGHNEEN, CAROLINE (Academica, 2009)
Diversity is essential for creativity and innovation, which are at the heart of engineering. Thus engineering can benefit from the richness and varied perspectives and expertise which individuals from different ethnicity, culture and gender can bring to problem-solving. Furthermore promoting diversity in the workforce provides greater access to talent by increasing the pool of qualified and skilled professionals. This chapter focuses on gender diversity as an area which has received considerable attention for many years from both the research community and policy makers. Researchers seek to explore the reasons for the continued under-representation of women in engineering in spite of numerous policies, initiatives and interventions. The subject will be explored through the role of female engineers in academia as it is the education sector which has the most critical influence on recruitment and retention, not just in academia itself but in the public and private sector generally. Using the ?tinkering, tailoring, transforming? model developed by Rees (1995), the chapter will explore the history of women in engineering, highlighting those interventions which appear to be having the greatest positive impact. In spite of the dearth of rigorous evaluation in terms of sustainability and scaleability, there is a growing body of evidence pointing to best practice in this area. This indicates that a significant shift in attitudes and culture is required in order to reach the critical mass of 30% when the process becomes embedded and sustainable.
PUBLISHED
Keywords: diversity in engineering, women in engineering